2019
DOI: 10.1016/j.ekir.2018.10.006
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of CKD of Unknown Etiology in Uddanam, India

Abstract: Introduction There were concerns raised regarding a high prevalence of chronic kidney disease (CKD) in Uddanam, a fertile subtropical low-altitude territory in the southern Indian state of Andhra Pradesh. The present study was undertaken to ascertain the prevalence of CKD, disease characteristics, and risk factor profile in this area. Methods We selected 2210 subjects (age >18 years) using multistage sampling. After obtaining demographic and anthropometric data, urinary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
48
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 24 publications
7
48
1
Order By: Relevance
“…Along with this observation from the registry data, the high prevalence of CKD found in the village where CKD screening was undertaken strengthens our suspicion of the endemic nature of CKD in this region. The prevalence of CKD was found to be 19% in the village, higher than most CKD prevalence estimates for India 6,7 and similar to the prevalence reported from the Uddanam region in Andhra Pradesh 8 and from endemic areas in Sri Lanka. 3 The only prior study that examined the etiology of CKD from our geographical region in India did so from a large urban center (Chennai) in 1993.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Along with this observation from the registry data, the high prevalence of CKD found in the village where CKD screening was undertaken strengthens our suspicion of the endemic nature of CKD in this region. The prevalence of CKD was found to be 19% in the village, higher than most CKD prevalence estimates for India 6,7 and similar to the prevalence reported from the Uddanam region in Andhra Pradesh 8 and from endemic areas in Sri Lanka. 3 The only prior study that examined the etiology of CKD from our geographical region in India did so from a large urban center (Chennai) in 1993.…”
Section: Discussionsupporting
confidence: 76%
“…Although estimates on the regional differences in the proportion of CKDu in the CKD population is not available from India, a high incidence of CKDu has been reported from the coastal areas of the state of Andhra Pradesh. 8 We found that the clinical characteristics of our patient population was comparable with the characteristics of CKDu patients from endemic areas in Sri Lanka and Central and South America as well as Uddanam in Andhra Pradesh, India. The patients were mostly from an underprivileged background, were engaged in farm labor or other forms of labor requiring significant physical activity, working in hot and humid climate, had shrunken echogenic kidneys with minimal proteinuria, and often presented with advanced CKD, with presumably minimally symptomatic or asymptomatic early stages ( Table 6).…”
Section: Discussionsupporting
confidence: 70%
“…A study by Tatapudi et al. [ 17 ] in Uddanam showed that the prevalence of eGFR < 60 mL/min per 1.73 m 2 ) was seen in 13.98% of their sample, while the prevalence of subjects having low eGFR and with proteinuria was 18.23%. The Indian CKD registry also reported that the highest number of CKD patients to be in the southern India [ 18 ].…”
Section: Discussionmentioning
confidence: 95%
“…The disease CKDu has been reported typically to affect young people. However a recent study from the Uddhanam region showed that only a minority of individuals (<20%) were <40 years of age, and women are equally affected 12 . We anticipate, therefore, that changes in GFR occurring in all age groups will need to be carefully determined.…”
Section: Study Population and Sample Size Considerationsmentioning
confidence: 96%
“…Unpublished cross-sectional data have indicated the existence of clusters with CKD prevalence ranging from 30% to 60%. A recent study estimated the prevalence of CKD at 18.3% in the area when proteinuria and/or decreased estimated glomerular filtration rate (eGFR) were taken as markers, and the cause could not be established in 13% 12 . This study, however, did not use the standard definition of CKD, which calls for confirmation after repeat testing.…”
mentioning
confidence: 99%